PENGEMBANGAN BAHAN AJAR DENGAN MENGGUNAKAN MODEL PBL UNTUK MENINGKATKAN KETERAMPILAN MEMBACA SISWA KELAS I SD MIS BIDAYATUL HIDAYAH 3 MEDAN - Khairunnisa Fitri; Ahmad Landong (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to develop teaching materials to improve the reading skills of first-grade students at MIS Bidayatul Hidayah 3 Elementary School, Medan. This research was motivated by students' low ability to recognize letters and spell words, as well as the limited use of engaging and appropriate teaching materials. The method used was research and development using the ADDIE model, but limited to the development stage: analysis, design, and development. The main focus of this research was to produce valid and suitable teaching materials. Data collection techniques used validation sheets from material experts and design experts. The validation results showed that the teaching materials received a feasibility score of 92.5% from the material experts and 93% from the design experts, thus categorizing them as